Simetria conforme e T-dualidade no modelo σ para cordas fechadas. - Pereira, Rheymisson Prado (2020)
Conformal symmetries determine the speci_x000C_fic form of the curved space-time string action, as well as its dimension D. When there are isometric dimensions, the obtained action manifests the T-Duality phenomenon, from which distinct equivalent backgrounds c